TAPE MODELING OF EUCALYPTUS STEM IN CROP-LIVESTOCK-FORESTRY INTEGRATION SYSTEMS - Cerqueira, Clebson Lima; Arce, Julio Eduardo; Vendruscolo, Diogo Guido Streck; Dolácio, Cícero Jorge Fonseca; da Costa Filho, Sérgio Vinícios Serejo; Tonini, Helio (Floresta, 2019)
This paper aims to evaluate and compare the mixed effects modeling and artificial neural networks in order to estimate the taper of eucalyptus in integrated Crop-Livestock-Forestry (iCLF) systems. The data were collected in an experimental area of iCLF, implanted by the Brazilian Company of Farming Research – EMBRAPA Agrossilvipastoril, located in the municipality of Sinop, Mato Grosso State, Brazil. To reach the proposed aim, 165 trees with 51 months of age were scaled for the taper modeling with mixed effects models and artificial neural networks. The performance of these techniques was evaluated through precision measurements and graphical analysis. Mixed effects modeling and artificial neural networks are efficient and recommended in the estimative of taper of eucalyptus in integrated Crop-Livestock-Forestry system; however, despite both evaluated techniques present accurate results in predicting the taper of the sampled trees, the artificial neural network predicts values with greater precision than the modeling of mixed effects.